Effect of Pilates based exercises on symptomatic knee osteoarthritis-A Randomized Controlled Trial - Nadia Saleem; Saima Zahid; Tahir Mahmood; Naeem Ahmed; Umer Maqsood; Muhammad Asad Chaudhary (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the effects of Pilates exercises on pain, knee range of motion and functional disability in women with knee osteoarthritis. Method: The double-blind randomised controlled trial was conducted at the National Orthopaedic Hospital, Bahawalpur, Pakistan, from April to September 2018, and comprised female patients with knee osteoarthritis. The subjects were selected randomised into control group A receiving isometrics and intervention group B receiving Pilates exercises. Both groups received one-hour sessions 3 times per week for 8 weeks. The groups were assessed at baseline and at the end of the 8th week using numeric pain rating scale and Western Ontario and McMaster Universities osteoarthritis index for pain and functionality level respectively. Data was analysed using SPSS 23. Results: Of 44 patients, there were 22(50%) in each of the two groups. Mean age of group B was 57.60±6.34 years, and it was 55.65±7.28 in group B. Mean body mass index of group B was 25.812±4.16, and it was 26.93±4.4 in group A. The study was completed by 40(91%) patients; 20(50%) in each of the two groups. Both groups showed significant improvement for pain, range of motion and physical function post-intervention (p<0.05). Group B showed significantly more improvement in terms of pain and physical function compared to group A (p<0.05). Conclusion: Pilates exercises were found to be more effective in the treatment of patients with knee osteoarthritis. Key Words: Isometrics exercise, Knee osteoarthritis, Knee pain, Pilates, Range of motion, WOMAC. Continuous...